PENGARUH LATIHAN FIVE-CONE SNAKE DRILL TERHADAP KELINCAHAN PADA TIM BOLAVOLI PUTRA FORTUNA KECAMATAN RAMBAH KABUPATEN ROKAN HULU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The problem in this research is the lack of agility of the Fortuna volleyball team players, Rambah District, Rokan Hulu Regency, seen when taking the ball very slowly and tending to be late when timing the ball. The purpose of this research was to determine the effect of the five-cone snake drill exercise on agility in the Fortuna men's volleyball team, Rambah District, Rokan Hulu Regency. The population in this research were Fortuna volleyball team players using a total sampling technique of 18 people. This type of research uses a pre-test and post-test before and after being given the instrument, namely the five-cone snake drill exercise, using data analysis techniques, namely the normality test and t test, to determine the effect of before and after being given the five-cone snake exercise. drills. Based on the analysis carried out, there was an average increase of 1.31. And based on inferential statistical analysis using the t-test, the t-test was 7.705 and the t-table was 1.734. It means that tcount > ttable, so it can be concluded that agility has an effect on the five-cone snake drill exercise which is needed to support the frequency when doing the exercise..Key Words: Five-Cone Snake Drill Exercise, Agility, Volleyball